2011
DOI: 10.1159/000334706
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Residual Antibiotics in Cryopreserved Heart Valve Allografts

Abstract: Introduction: Cardiovascular allografts are systematically incubated in antibiotics for their decontamination, and the antibiotics are removed before allograft implantation. We studied the occurrence of antibiotic residues in allograft valves. Methods: 12 experimental allografts were analyzed in this study. The concentration of the residual antibiotics was determined by high-performance liquid chromatography and the results were expressed as microgram per gram of allograft tissue. Results: The initial analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Tissue samples decontaminated with antibiotic cocktails are a specific type of microbiological sample that may present bacteriostatic and/or fungistatic properties [8] , [15] . The intrinsic properties of the tissues, such as enzymatic activity, immunologic events, and presence of antimicrobial peptides [16] , which are well described in the skin [17] , cornea [18] , and amniotic membrane [19] , may be exacerbated by the presence of residual antibiotics following tissue decontamination with antibiotic cocktails [7] , [8] , [20] . The European and US Pharmacopoeias indicate eliminating any factor that may interfere with microbial growth during sterility testing from samples [9] , [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Tissue samples decontaminated with antibiotic cocktails are a specific type of microbiological sample that may present bacteriostatic and/or fungistatic properties [8] , [15] . The intrinsic properties of the tissues, such as enzymatic activity, immunologic events, and presence of antimicrobial peptides [16] , which are well described in the skin [17] , cornea [18] , and amniotic membrane [19] , may be exacerbated by the presence of residual antibiotics following tissue decontamination with antibiotic cocktails [7] , [8] , [20] . The European and US Pharmacopoeias indicate eliminating any factor that may interfere with microbial growth during sterility testing from samples [9] , [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Biodistribution studies have shown VCN to be widely distributed into most body organs after administration via intravenous injection or infusion [3], including cerebrospinal fluid (CSF) [4], heart valves [5], lungs [6] and interstitial fluid (ISF) [7]. As a consequence, and for therapeutic drug monitoring purposes, it is important to develop a sensitive and selective method for analysing and quantifying VCN in a range of different biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…31,70 Perhaps even worse, there is a risk that the antibiotics can cause severe allergic or toxic reactions in tissue recipients. 71,72 We were unable to find current studies that reported on this issue and its potential to cause serious clinical consequences. There is a risk that recipients who have an allergy to specific antibiotics could develop allergic reactions after transplantation as a result of extremely high concentrations of antibiotics in the tissues.…”
Section: Disinfection Of Cardiovascular Allograftsmentioning
confidence: 94%